HUBUNGAN SELF ESTEEM DAN ADVERSITY QUOTIENT DENGAN KEMANDIRIAN BELAJAR PADA SISWA KELAS X DI MAN 20 JAKARTA TIMUR - Patria, Tasya Meyco; J. Silaen, Sondang Maria (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
This study aims to determine the relationship between self esteem and adversity quotient with the learning independence of class X students at MAN 20 East Jakarta. The subjects in this study were 103 class students. The sampling technique uses simple random sampling technique and data collection tools in the form of questionnaire scale. Researchers used two measuring instruments namely Rosenberg self esteem scale and Adversity Response Profile. This type of research is quantitative research. The results showed the research data on the hypothesis using reggression and the enter method between self esteem and adversity quotient variables with learning independence obtained correlation coefficient (R) of 0.268 and p = 0.24> 0.05. Which means the alernative hypothesis (Ha) which reads, "there is relationship between self esteem and adversity quotient with the independence of class X students at MAN 20 East Jakarta".